Chemical modification of edible sodium caseinate: A new grafting method of oleic acid. Characterization and thermal properties of the conjugate. (15th May 2023) - Tichané, Teddy; Viora, Laurianne; Garric, Xavier; Klem-Robin, Emmanuel; Coudane, Jean; Van Den Berghe, Hélène
Highlights: A new synthesis method for grafting oleic acid onto sodium caseinate is described. A fine characterization of the conjugate is developed, especially by DOSY NMR. A high substitution degree (24 wt%) is obtained, measured by 1 H NMR. The thermal properties of the conjugate are evaluated and discussed. Abstract: Sodium caseinate is a well-known amphiphilic protein derived from natural products currently used for the preparation of edible films. To improve some properties, especially to decrease the hydrophilicity and water solubility of the caseinate, the covalent grafting of a hydrophobic edible fatty acid, namely oleic acid, onto caseinate, appears to be a solution. We describe a new synthesis method for the chemical modification of sodium caseinate involving the synthesis of an acid chloride derivative from oleic acid and a phase transfer catalysis reaction in a biphasic medium. Under these conditions, free amine and alcohol groups of the caseinate are likely to be grafted with a fairly high (>50 %) substitution degree. The caseinate derivative is finely characterized, in particular by DOSY NMR, to assess the formation of a casein/oleic acid grafted compound as well as the absence of residual oleic acid.